Systematic characterization of Puerariae Flos metabolites in vivo and assessment of its protective mechanisms against alcoholic liver injury in a rat model - Qu, Jialin; Chen, Qiuyue; Wei, Tianfu; Dou, Ning; Shang, Dong; Yuan, Dan (Frontiers in Pharmacology, 2022)
Puerariae Flos, a representative homology plant of medicine and food for alcoholism, has long history of clinical experience and remarkable curative effect in the treatment of alcoholic liver disease (ALD). However, its effective forms and hepatoprotective mechanism are remained unknown. In the present study, a strategy based on UPLC-QTOF MS combined with mass defect filtering technique was established for comprehensively mapping the metabolic profile of PF in rat plasma, urine, bile and feces after oral administration. Furthermore, the absorbed constituents into plasma and bile with a relative high level were subjected to the network analysis, functional enrichment analysis and molecular docking to clarify the potential mechanism. Finally, the therapeutic effect of PF on ALD and predicted mechanisms was further evaluated using a rat model of alcohol-induced liver injury and Western blot analysis. In total, 25 prototype components and 82 metabolites, including 93 flavonoids, 13 saponins and 1 phenolic acid were identified or tentatively characterized in vivo. Besides, glucuronidation, sulfation, methylation, hydroxylation and reduction were observed as the major metabolic pathways of PF. The constructed compound-target-pathway network revealed that 11 absorbed constituents associated with the 16 relevant targets could be responsible for the protective activity of PF against ALD by regulating 9 pathways attributable to glycolysis/gluconeogenesis, amino acid metabolism, lipid regulation as well as inflammation and immune regulation. Besides, 4 active ingredients (6''-O-xylosyltectoridin, genistein-7-glucuronide-4'-sulfate, tectoridin-4'-sulfate and 6''-O-xylosyltectoridin-4'-sulfate) as well as 2 target genes (MAO-A and PPAR-α) were screened and validated to play a crucial role with good molecular docking score. The present results not only increase the understanding on the effective form and molecular mechanism of PF mediated protection against ALD, but also promote better application of PF as supplement food and herbal medicine for the treatment of ALD.